Analysis of hybrid waste-to-energy for medium-sized cities - Balcazar, Juan Galvarino Cerda [UNESP]; Dias, Rubens Alves [UNESP]; Balestieri, José Antônio Perrella [UNESP] (My University, 2013)
Urban centers have a huge demand for electricity and the growing problem of the solid waste management generated by their population, a relevant social and administrative problem. The correct disposal of the municipal solid waste (MSW) generated in cities is one of the most complex engineering problems that involves logistics, safety, environmental and energetic aspects for its adequate management. Due to a national policy of solid wastes recently promulgated, Brazilian cities are evaluating the technical and economic feasibility of incinerating the non-recyclable waste. São José dos Campos, a São Paulo State industrialized city, is considering the composting of organic waste for biogas production and mass incineration of non-recyclable waste. This paper presents a waste-to-energy system based on the integration of gas turbines to a MSW incinerator for producing thermal and electric energy as an alternative solution for the solid waste disposal in São José dos Campos, SP. A technical and economic feasibility study for the hybrid combined cycle plant is presented and revealed to be attractive when carbon credit and waste tax are included in the project income. © 2013 Elsevier Ltd.
Keywords: Hybrid combined cycle; Incineration; Municipal solid waste; Waste-to-energy; Alternative solutions; Combined cycle; Complex engineering problems; Economic feasibilities; Municipal solid waste (MSW); Non-recyclable waste; Waste to energy; Waste-to-energy systems; Combined cycle power plants; Economic analysis; Waste disposal; Waste incineration; biogas; combined heat and power; composting; electricity; feasibility study; incineration; logistics; municipal solid waste; safety; solid waste; waste management; Brazil; Santa Catarina; Sao Jose; Sao Paulo [Brazil]; Sao Paulo [Sao Paulo (STT)]